Antimicrobial Efficacy of Cefoperazone-Salbactam Plus Tigecycline versus Cefoperazone-Salbactam Against Respiratory Pathogens and Their Effect on Laboratory Indices - Shaukat, Sundas; Irfan, Zona; Arif, Haseeba; Sadiq, Sidra; Bakhtiar, Shehnaz; Ismail, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the antimicrobial efficacy of cefoperazone plus tigecycline versus cefoperzone and their effect on biochemical indices.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Pathology, Rehman Medical Institute, Peshawar Pakistan, Nov 2022 to May 2023.Methodology: Patients of either gender with age >20 years having intensive care unit stay of >72 hours having clinical and radiological evidence of hospital acquired respiratory infection were included in the trial. A non-randomized convenience sampling technique was employed. Group CT patients received a combination of cefoperazone-sulbactam plus tigecycline intravenously while Group C participants received only cefoperazone-salbactam. Demographics, inflammatory markers,pathogens, treatment effectivity were recorded.Results: Mean age of participants in Group CT was 57.59±6.08 years as compared to 56.37±6.87 years in Group C. Pseudomonas aeruginosa was the most common pathogen identified in 30(23.8%) patients. CRP, WBC’s and PCT was significantly reduced after antibiotic treatment in both groups with a p-value of